2021
DOI: 10.1126/science.aay2784
|View full text |Cite
|
Sign up to set email alerts
|

Parallel molecular mechanisms for enzyme temperature adaptation

Abstract: The mechanisms that underly the adaptation of enzyme activities and stabilities to temperature are fundamental to our understanding of molecular evolution and how enzymes work. Here, we investigate the molecular and evolutionary mechanisms of enzyme temperature adaption, combining deep mechanistic studies with comprehensive sequence analyses of thousands of enzymes. We show that temperature adaptation in ketosteroid isomerase (KSI) arises primarily from one residue change with limited, local epistasis, and we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 256 publications
5
63
0
Order By: Relevance
“…The results revealed no enrichment of faster reactions with colder growth temperatures, and thus did not support increased rate with decreasing environmental temperature as a prevalent adaptation in nature. Further, we found that most rate variation for the enzyme ketosteroid isomerase (KSI) is not accounted for by TGrowth despite strong prior evidence for temperature adaptation within its active site (Pinney et al, 2021). In contrast, a similar broad analysis revealed that stability correlates with TGrowth, as expected.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The results revealed no enrichment of faster reactions with colder growth temperatures, and thus did not support increased rate with decreasing environmental temperature as a prevalent adaptation in nature. Further, we found that most rate variation for the enzyme ketosteroid isomerase (KSI) is not accounted for by TGrowth despite strong prior evidence for temperature adaptation within its active site (Pinney et al, 2021). In contrast, a similar broad analysis revealed that stability correlates with TGrowth, as expected.…”
Section: Introductionsupporting
confidence: 53%
“…Additionally, adaptive paths towards stability may be more abundant and more accessible than analogous paths towards rate enhancement, given that each protein may be stabilized individually through a wide variety of mechanisms (Hart et al, 2014) and less constrained by biological context than an enzyme evolving synergistically with complex metabolic networks. The recent discovery of 158,184 positions from 1005 enzyme families that vary with growth temperature may further expand our understanding of the molecular strategies that underlie protein stabilization (Pinney et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond precision medicine, metagenomic sequencing efforts have yielded millions of protein sequences with potential novel ll functions and properties, but <1% have been functionally characterized (Galperin and Koonin, 2010;Harrington et al, 2007;Popovic et al, 2017). Mapping stabilities across this vast sequence space provides an opportunity to explore how constraints of protein physical architecture intersect with evolutionary processes (Harms and Thornton, 2013) and to understand how molecules adapt to the selective pressures imposed by changing environmental conditions such as temperature (Pinney et al, 2021). By exploring the diversity of not only extant sequences but also reconstructed sequences with advantageous properties, we can additionally learn from the past to inform the design of future proteins (Gumulya and Gillam, 2017).…”
Section: Building Biological Understandingmentioning
confidence: 99%
“…Physiological exploration of the >332 human proteins (Gordon et al, 2020) which may interact with SARS-CoV-2 proteins is crucial. A global collaboration may be necessary to analyze the value of each nucleotide in the ~30KB single stranded RNA genome 428 of SARS-CoV-2 because even a single amino acid structural change can have profound impact 429 on function. Precedence for this rigor may have started with in the incisive minutiae of mutagenesis 430 applied to beta lactamase.…”
Section: Back To Basic Sciencesmentioning
confidence: 99%